The Effect of Drying Method on The Antioxidant Activity of The Flesh of Nutmeg - Fita Selonni (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2021)
Nutmeg pulp is one part of the nutmeg plant that contain antioxidant to prevent free radicals in the body. Nutmeg pulp contains secondary metabolites of the flavonoid class which have function as antioxidant. This study was conducted to determine the effect of drying the nutmeg pulp on the level of antioxidant activity using the DPPH method. After measuring the antioxidant activity of wind-dried and oven–dried nutmeg using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method, the results showed that the antioxidant activity (IC50) of wind dry is 116,952 µg/mL and oven dry is 219,2 µg/mL. The result of one-way Anova data analysis obtain p-value (p)